Genome-Wide Identification and Analysis of Grape Aldehyde Dehydrogenase (ALDH) Gene Superfamily - Zhang, Yucheng (Public Library of Science, 2012)
BACKGROUND: The completion of the grape genome sequencing project has paved the way for novel gene discovery and functional analysis. Aldehyde dehydrogenases (ALDHs) comprise a gene superfamily encoding NAD(P)(+)-dependent enzymes that catalyze the irreversible oxidation of a wide range of endogenous and exogenous aromatic and aliphatic aldehydes. Although ALDHs have been systematically investigated in several plant species including Arabidopsis and rice, our knowledge concerning the ALDH genes, their evolutionary relationship and expression patterns in grape has been limited. METHODOLOGY/PRINCIPAL FINDINGS: A total of 23 ALDH genes were identified in the grape genome and grouped into ten families according to the unified nomenclature system developed by the ALDH Gene Nomenclature Committee (AGNC). Members within the same grape ALDH families possess nearly identical exon-intron structures. Evolutionary analysis indicates that both segmental and tandem duplication events have contributed significantly to the expansion of grape ALDH genes. Phylogenetic analysis of ALDH protein sequences from seven plant species indicates that grape ALDHs are more closely related to those of Arabidopsis. In addition, synteny analysis between grape and Arabidopsis shows that homologs of a number of grape ALDHs are found in the corresponding syntenic blocks of Arabidopsis, suggesting that these genes arose before the speciation of the grape and Arabidopsis. Microarray gene expression analysis revealed large number of grape ALDH genes responsive to drought or salt stress. Furthermore, we found a number of ALDH genes showed significantly changed expressions in responses to infection with different pathogens and during grape berry development, suggesting novel roles of ALDH genes in plant-pathogen interactions and berry development. CONCLUSION: The genome-wide identification, evolutionary and expression analysis of grape ALDH genes should facilitate research in this gene family and provide new insights regarding their evolution history and functional roles in plant stress tolerance.